Kondol (Benincasa hispida, Cogn.) as meat extender in cull chickenburgers (Gallus gallus domesticus, Linn.) - Cayme, Ma. Fides M.
Using a preselected chickenburger recipe, cull chickenburger with varying amount (10%, 20%, 30%) of kondol (Benincasa hispida, Cogn.) were prepared. Frozin cull chicken dark meat was chosen as the main raw material primarily because of its high protein content. Its low % water holding capacity was remedied by the use of a binder and by the addition of phosphates. The % water holding capacity and % (diameter) shrinkage decreased while the % cooking loss increased when the level of kondol was increased. Improved tenderness and juiciness were attained with the higher levels of kondol. Chicken flavor was the same regardless of the level of kondol used. The chickenburger with 20% kondol was regarded as the most acceptable; the one without kondol, the least acceptable. Cost reduction of P 3.40/kg (February, 1984) was achieved as the level of kondol was increased up to 30%.